Pengaruh Kegiatan Ekstrakulikuler Terhadap Motivasi Belajar Siswa di SMAN 4 Probolinggo - I Ketut Mahardika; Amalia Melinda; Nanda Tiara Putri; Zakiyah Izza Avkarinah; Rizka Elan Fadilah; Firdha Yusmar (Peneliti.net, 2022)
In this study raised several main issues, namely: (1) extracurricular activities at SMAN 4 Probolinggo, (2) Increasing student motivation at SMAN 4 Probolinggo, (3) The effect of extracurricular activities carried out on students' learning motivation. In answering this research, the information obtained is based on interviews. The population is class 11B students at SMAN 4 Probolinggo, namely 36 students. Then the number of students who were taken as samples in this study were taken 11 people from SMAN 4 Probolinggo students. From the results of data processing, the results of extracurricular activities at SMAN 4 Probolinggo are very effective in increasing students' learning motivation. But the division of time between study and rest, considering that these students are still in the learning process so they need the support of all parties from the survival of the school in the future to increase learning motivation